Pengembangan E-Modul Flipbook Berbasis Problem Based Learning Terhadap Kemampuan Komunikasi Matematis Siswa - Tasya Anindya Rahma; Rhomdani, Rohmad Wahid (STAIN Bengkalis, 2025)
This study aims to develop and evaluate a flipbook-based e-module integrated with the Problem Based Learning (PBL) approach to enhance high school students' mathematical communication skills in scatter plot material. Using the Research and Development (R&D) method with the Plomp model, the study consisted of three stages: preliminary research, prototyping, and assessment. The subjects were 11th-grade students (class XI.4) at SMAN 5 Jember. Validation results from experts showed that the e-module was highly valid, with a score of 88.75%. Practicality tests via teacher and student questionnaires yielded an average score of 90%, indicating that the module is highly practical for classroom use. Effectiveness was measured by comparing pretest and posttest scores, revealing an average N-Gain of 0.54 (moderate category). The findings demonstrate that the developed PBL-based flipbook e-module is feasible, practical, and effective for implementation in learning, significantly improving students' mathematical communication skills.